APPLICATION OF POCKET DEVICE SENSORS FOR MOVING OBJECT POSITIONING IN AIR SPACE - Ostroumov, Ivan; Protsenko, Eizhena; Rudenko, Mykyta (Proceedings of National Aviation University (archive), 2019)
Purpose:Localization and positioning of movable objects in air space are one of the main navigation tasks. In our research, we consider the application of accelerometers and gyroscopes sensors for finding the position of the object in space using the personal pocket device. The personal pocket device is plugged to the object body and location of an object is associated with the pocket device location. The personal pocket device includes sensors and performs measurements, but localization function is performed at the remote ground station. The data exchange between the pocket device and computation service is supported by WiFi network. Methods:Object position detection is grounded on inertial navigation approach.Also, we use experimental research and statistical analysis of the obtained data. Results:developed math model is applied in software that supports data exchange with android compliant personal pocket devices.The software initiates measurements of acceleration and object orientation in space at personal pocket device side and estimates object position in a local Cartesian coordinate system by inertial navigation approach.Discussion: the proposed approach can be used in new positioning systems structure for tracking of small movable objects in air space.